2004
DOI: 10.1097/00004694-200409000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Gait Patterns After Fracture of the Femoral Shaft in Children, Managed by External Fixation or Early Hip Spica Cast

Abstract: The authors prospectively studied three-dimensional kinematics and kinetics of gait in children recovering from a closed, isolated, nonpathologic fracture of the femoral diaphysis, who had been randomly assigned to management by monolateral external fixation or early hip spica casting. The aims were to investigate the gait patterns soon after injury and at 2 years after injury. Children treated with external fixation, walking with the external fixator in situ, demonstrated asymmetric gait abnormalities in all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 23 publications
2
13
0
Order By: Relevance
“…Dameron and Thompson 8 provided the first available detailed description of spica casting application and short-term outcomes in 1959. Since these initial articles, five randomized control trials, 9 - 13 37 cohort studies, 1 , 14 50 37 retrospective reviews, 8 , 51 86 13 technique articles, 87 99 and three guidelines 4 , 100 , 101 have been published relating to the use of spica casting in paediatric diaphyseal femur fractures. This review focuses on three major aspects of over five decades of literature: 1) fracture position tolerance to prevent unacceptable limb alignment; 2) complications associated with spica casts; and 3) technique and material recommendations.…”
Section: Overview Of the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Dameron and Thompson 8 provided the first available detailed description of spica casting application and short-term outcomes in 1959. Since these initial articles, five randomized control trials, 9 - 13 37 cohort studies, 1 , 14 50 37 retrospective reviews, 8 , 51 86 13 technique articles, 87 99 and three guidelines 4 , 100 , 101 have been published relating to the use of spica casting in paediatric diaphyseal femur fractures. This review focuses on three major aspects of over five decades of literature: 1) fracture position tolerance to prevent unacceptable limb alignment; 2) complications associated with spica casts; and 3) technique and material recommendations.…”
Section: Overview Of the Literaturementioning
confidence: 99%
“…We found 53 articles identifying their shortening tolerance at initial casting or at follow-up. 8 , 9 , 12 - 21 , 23 , 25 - 27 , 29 - 31 , 36 , 38 , 39 , 41 , 42 , 45 - 48 , 50 , 53 , 55 , 56 , 60 , 62 - 67 , 69 , 71 , 73 , 74 , 76 , 79 - 83 , 89 , 97 , 100 , 102 , 103 The most recent (2009) American Academy of Orthopaedic Surgeons Guidelines for the management of diaphyseal femur fractures in the paediatric population is to use spica casting for those with < 2 cm of shortening. 4 The mean and sd of all studies which specified their tolerances is shown in Figure 1 .…”
Section: Fracture Position Tolerancementioning
confidence: 99%
“…Gait adaptations such as abnormal kinematics at the hip and knee (described as antalgic strategies), asymmetry between loading patterns and alterations to temporospatial characteristics have been identified in individuals with external fixation of the lower limb. 6,7 Joint stiffness, laxity of the knee and transient foot drop have also been reported in patients treated by definitive external fixation. 810 Alterations to an individual’s natural joint kinetics during treatment may lead to loss of function and abnormal loading of the fractured limb.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16][17][18][19][20][21][22][23] Typical problems with the use of unilateral fixators include malreduction, [13][14][15]18 loss of reduction, delayed healing, 21,23 pin tract infections, 12,13,16,21,24 cosmetic concerns with pin scarring, 25 need to place intra-articular half-pins in the distal femoral epiphyses, 3 and refracture after fixator removal. 16,19,21 Most of these complications seem technical in nature.…”
Section: Discussionmentioning
confidence: 99%
“…By avoiding the need for skeletal traction followed by spica casting, significantly earlier mobilization with normalization of the gait pattern has been reported with the use of external fixation for femoral fractures. 22,27,28 There are drawbacks associated with the use of an Ilizarov external fixator. These include a need to be familiar with the use of the device; however, other external fixator systems can be used if the principles outlined above are followed.…”
Section: Discussionmentioning
confidence: 99%